STUDY OF THE UNLOADING AND SELECTION PROCESS OF ENERGY WILLOW CUTTINGS FOR THE CREATION A PLANTING MACHINE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article highlights the problems of ensuring continuous unloading of energy willow cuttings from slotted bunkers.  During the free discharge of rod-like bodies, such phenomena as crypt formations, distortions, pinching occur, which stop the discharge under the action of gravity.  Finding such parameters, under which the system will work evenly and without stops, will make it possible to automate many processes related to working with such material, in particular, when developing a piecemeal selection mechanism for a planting machine.  The study revealed and analyzed the possible forms of vaults that are formed during unloading from creating obstacles to movement.  As a hopper model, for unloading cuttings, a slotted hopper in the form of two walls located at angles to the horizontal plane is considered.  These walls form an unloading slot with adjustable width of the unloading window and an adjustable tilt angle.  During the study, vaults were recorded, which are formed at different parameters of the bunker during free unloading.  As research has shown, in order to ensure uninterrupted unloading of cuttings, there is such a width of the unloading window of the hopper, which will ensure uniform pouring of cuttings without crypt formations and stops associated with this process.  The analysis of continuous discharge of rod-like material established that for cuttings of energy willow, the width of the window, which ensures continuous discharge, is 8-12 cm.